PRINCIPAL POLICY EVALUATION METHOD IN IMPROVING THE QUALITY OF EDUCATION AT AL-HAMIDY KEBON TALO HIGH SCHOOL - novi, noviatunpadilah (An-Nahdlah: Jurnal Pendidikan Islam, 2024)
This study aims to describe the method of evaluating the principal's policy in improving the quality of education at Madrasah Aliyah Al-Hamidy Kebon Talo. This study uses a descriptive qualitative method. Data collection techniques are carried out by interviews, observations, and documentation. The sources in this study were the Principal, Wakakurikulum, and Teachers of MA Al-Hamidy. Data were analyzed by data reduction, data presentation, and verification. The results of the study are that in improving the quality of education at MA Al-Hamidy Kebon Talo, an appropriate policy evaluation method is needed by the principal. Because the evaluation helps in improving previous policies by considering their impacts. The principal needs to involve school residents in discussions to ensure that the policies taken are right on target. One of the indicators of the results of the principal's policy evaluation in improving the quality of education is the improvement of facilities and teacher competence in the IT field.